FEATURES OF THE RUSSIAN INDUSTRIAL PRODUCTS MARKETING POTENTIAL IN THE MARKETS OF INDIA - S. Chernikov (Publishing House of the State University of Management, 2016)
Thе article discusses the most inportant areas to focus efforts of supporting the access of Russian industrial goods to the markets of India. The product groups with the greatest marketing potential are considered. Also an overview of the current state of russian-indian relations is done in the light of foreign policy priorities pragmatic rethinking in both countries on the basis of the changed geopolitical environment as a factor of influence on the trade of the countries under consideration.